Conflicts between work and family and displaced aggression with working parents in South Korea: An exploratory study - Kim, Eunha; Shin, Yun Jeong; Kim, Jisu (Journal of Comparative Family Studies, 2019)
Because the related domains of work-family conflict and family-work conflict have become significant issues for Korean dual-career couples, we examined whether the satisfaction of autonomy needs (feelings of agency, volition, and initiating one’s own actions) in a marriage would moderate the relationship between work-family conflicts and displaced aggression toward family. In addition, we investigated whether such moderating effects would be different for men and women. The results revealed that the satisfaction of autonomy needs in marital relationships buffered the negative effects of work-family conflicts on displaced aggression toward family, although this effect was significant only for men. In contrast, the satisfaction of autonomy needs had a moderating effect on the association between family-work conflicts and displaced aggression toward family for women, but not for men.
Keywords: Displaced aggression toward family; Family-work conflict; Satisfaction of autonomy needs; Work-family conflict